CD4+ AND CD8+ T-CELLS EXPRESSING INTERFERON GAMMA IN ACTIVE PULMONARY TUBERCULOSIS PATIENTS - Tambunan, Betty Agustina; Priyanto, Hery; Nugraha, Jusak; Soedarsono, Soedarsono (African Journal of Infectious Diseases (AJID), 2018)
Background: Tuberculosis (TB) is a global health problem. Immune response through CD4+ and CD8+ T cells is needed to produce Interferon gamma (IFN-γ), a cytokine eliminate Mycobacterium tuberculosis. We aimed to compare the cellular immune response based on the percentage of CD4+ and CD8+ T cells expressing interferon gamma in active pulmonary tuberculosis patients before and after 2 months of tuberculosis treatment. Methods: It is a longitudinal cohort study included 12 patients with new active pulmonary TB of the Pulmonary Hospital, Surabaya. The CD4+ and CD8+ T cells expressing interferon gamma was measured by flow cytometry method. Results: The mean CD4+ interferon gamma percentage of new active pulmonary TB before treatment was higher than 2 months after tuberculosis treatment (4.48% vs. 1.52%) and there was a significantly decreased (p = 0.025). The mean CD8+ interferon gamma percentage of new active pulmonary TB before treatment was higher than 2 months after tuberculosis treatment (3.56% vs. 2.89%) but not significantly decreased (p = 0.186). Conclusions: The mean CD4+ IFN-γ percentage of new active pulmonary TB before treatment was higher than 2 months after treatment, suggesting that CD4+ T cells expressing IFN-γ play a role in protection against pulmonary TB infectio